Kashmir and the Northern Areas of Pakistan: boundary-making along contested frontiers - Kreutzmann, Hermann (ERDKUNDE, 2008)
Boundaries as known to us and delineated on maps were introduced in the Hindukush-Karakoram-Himalaya ranges in the late 19th century. The results of the “Great Game” have created major sources for conflicts and war. Kashmir, the Siachin Glacier and the Northern Areas of Pakistan are prime examples of virulent disputes which are still hot issues today. This contribution aims to identify the historical background and stage-wise developments which led to the present stalemate. The status of the Northern Areas is a legacy from the British Raj and is rooted in the overall Kashmir conflict arena. The present contest for more autonomy and representation in the federal institutions is linked to the country’s uneven participatory approach that is reflected in spatial entities confronted with extra-constitutional status, application of colonial rules, and implementation of indirect rule in tribal areas as well as direct administration of disenfranchised people by the centre of power. The process of slowly adjusting and changing the position of the Northern Areas has created conflicts and confrontation along different lines. Borders are identifiable results of conflict constellations and administrative attempts for their resolution. The region studied represents a case in point for restructuring territories that remain under dispute. Besides international conflicts over space there are internal disputes on different levels of society. Contested administrative setups, demands for equitable quota systems and legitimate representation in public services, regionalism and sectarian clashes form the spectrum of social, spatial and political boundary-making in the Northern Areas. The frontiers are contested grounds and boundary-making is a continuing process. This contribution aims at understanding the actors, driving forces and stakeholders in their respective arenas of contest.